The Implementation of The Everyone is Teacher Here Model Using Short Card media to Improve the Student Learning Achievement and Activities - Anggraini, Lisa; Yanti, Wita Tri (Journal of Learning Improvement and Lesson Study, 2025)
This study aims to improve the Biology learning achievement and to overcome the student boredom through the application of the Everyone Is Teacher Here (EITH) learning model using Short Card media on the Kingdom Animalia material. This study used the Classroom Action Research (CAR) with 4 stages: planning, implementation, observation, and reflection. The subjects of the study were 34 students of grade X at one of the State Senior High School 2 Sungai Penuh. The study was conducted in three cycles. The data were collected by using the learning outcome tests, observation of the teacher skills and student activities, and documentation. Then, these data were analyzed descriptively, quantitatively and qualitatively. The results showed that the classical learning completeness increased from 50.00% in Cycle I to 73.53% in Cycle II, and reached 88.24% in Cycle III. The student activities and the teacher skills also increased to reach the very good category. Thus, it can be concluded that the application of the EITH model using Short Card is effective in improving the learning achievement and overcoming the student boredom on the material of Kingdom Animalia